Testosterone Upregulates the Expression of Mitochondrial ND1 and ND4 and Alleviates the Oxidative Damage to the Nigrostriatal Dopaminergic System in Orchiectomized Rats. (24th August 2017) - Yan, Wensheng; Kang, Yunxiao; Ji, Xiaoming; Li, Shuangcheng; Li, Yingkun; Zhang, Guoliang; Cui, Huixian; Shi, Geming
Abstract : Testosterone deficiency, as a potential risk factor for aging and aging-related neurodegenerative disorders, might induce mitochondrial dysfunction and facilitate the declines of the nigrostriatal dopaminergic system by exacerbating the mitochondrial defects and increasing the oxidative damage. Thus, how testosterone levels influence the mitochondrial function in the substantia nigra was investigated in the study. The present studies showed that testosterone deficiency impaired the mitochondrial function in the substantia nigra and induced the oxidative damage to the substantia nigra as well as the deficits in the nigrostriatal dopaminergic system. Of four mitochondrial respiratory chain complexes, castration of male rats reduced the activity of mitochondrial complex I and downregulated the expression of ND1 and ND4 of 7 mitochondrial DNA- (mtDNA-) encoded subunits of complex I in the substantia nigra. Supplements of testosterone propionate to castrated male rats ameliorated the activity of mitochondrial complex I and upregulated the expression of mitochondrial ND1 and ND4. These results suggest an important role of testosterone in maintaining the mitochondrial function in the substantia nigra and the vulnerability of mitochondrial complex I to testosterone deficiency. Mitochondrial ND1 and ND4, as potential testosterone targets, were implicated in the oxidative damage to the nigrostriatal dopaminergic system.